2013
DOI: 10.1088/1752-7155/7/1/017113
|View full text |Cite
|
Sign up to set email alerts
|

A mobile instrumentation platform to distinguish airway disorders

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) are distinct but clinically overlapping airway disorders which often create diagnostic and therapeutic dilemmas. Current strategies to discriminate these diseases are limited by insensitivity and poor performance due to biologic variability. We tested the hypothesis that a gas chromatograph / differential mobility spectrometer (GC/DMS) sensor could distinguish between clinically well-defined groups with airway disorders based on the volatile organic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Differences in exhaled breath condensate signals may allow us to differentiate between subjects with and without asthma, and may further allow us to eventually differentiate asthma from other airway diseases such as chronic obstructive pulmonary disease. [148][149][150] In our own clinics at the University of California, Davis, we routinely use measures of FeNO, a known marker of eosinophilic airway inflammation, as one part of our assessment of the patient's control of disease based on the American Thoracic Society's published clinical practice guidelines published in 2011. The technology for measuring FeNO has also been standardized.…”
Section: Future Directions In Understaning Viruses Non-allergen Asthmentioning
confidence: 99%
“…Differences in exhaled breath condensate signals may allow us to differentiate between subjects with and without asthma, and may further allow us to eventually differentiate asthma from other airway diseases such as chronic obstructive pulmonary disease. [148][149][150] In our own clinics at the University of California, Davis, we routinely use measures of FeNO, a known marker of eosinophilic airway inflammation, as one part of our assessment of the patient's control of disease based on the American Thoracic Society's published clinical practice guidelines published in 2011. The technology for measuring FeNO has also been standardized.…”
Section: Future Directions In Understaning Viruses Non-allergen Asthmentioning
confidence: 99%
“…Using gas chromatography coupled with a differential mobility spectrometer sensor (GC‐DMS) to analyse VOCs in the exhaled breath samples of 13 individuals with asthma, five subjects with COPD and 13 healthy controls, Schivo et al. demonstrated that it was possible to differentiate patients with asthma from healthy individuals. However, the most discriminant compounds in this analysis could not be identified because there was no analyte diagnostic library for the GC‐DMS methodology at the time of the study in spite of the parameters which could be used for species identification.…”
Section: Discussionmentioning
confidence: 99%
“…In the aforementioned study performed by Schivo et al. , the authors hypothesized that GC‐DMS could be used to differentiate between individuals with asthma and individuals with COPD, using VOC profiles. However, they observed that after analysing the VOC profiles, it was not possible to distinguish between COPD and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…GC-IMS allows the detection of VOCs down to ultratrace level (µg/L – to pg/L – range). For years, IMS has been used to discover potential discriminatory breath VOC in lung cancer,69 70 chronic obstructive pulmonary disease (COPD)71 72 and asthma 72. Sampling takes place using a Spiroscout spirometer.…”
Section: Breath Profilingmentioning
confidence: 99%